Proposal for support to people with modified capacity from social work. the case of guardian entities - Dorado Barbé, Ana; González Casas, David; Rivera Alvarez, Joaquín María; Sojo Belinchón, Rocío (Política y Sociedad, 2021)
The United Nations Convention on the Rights of Persons with Disabilities (2006) substantially modified the scenario of disability. This transformation is located in a change of perspective in reference to stop considering disability under a rehabilitative biosanitary model, to move to a model that considers people with disabilities as subjects entitled to rights and in which public powers stand out in their obligation to guarantee that the exercise of said rights is effective and full. Based on this, it reflects on the new legal and social scenario and proposes a model of social care to be developed by Guardianships from the perspective of Social Work. This proposal aims to unite the new intervention paradigms and serve as a methodological tool for Guardianship Entities in Spain in the 21st century.